Chemical investigation of methanol extracts of Swietenia mahagoni leaves and its antioxidant activity - Masendra, Masendra; Purba, Brandon Aristo Verick; Arisandi, Rizki; Lukmandaru, Ganis (Masyarakat Peneliti Kayu Indonesia, 2014)
Swietenia mahagoni is among the species of trees used by the Indonesian Government for the purpose of afforestation and timber production through Perhutani Enterprise. The common use of this species as wood products has prompted investigating the chemical properties of its leaves. Based on this background, this study aimed at investigating the methanol extracts of both 2- and 3-year old S. mahagoni leaves extractives together with its antioxidants and phenols contents. The antioxidant activity was conducted through the DPPH (1,1-diphenyl-2-picrylhydrazyl) method, while the total phenolic and flavonoid content were measured through Folin-Ciocalteu and AlCl3 methods, respectively. Additionally, 24 compounds were characterized by the GC-MS, and were grouped into phenolics, fatty acids and hydrocarbons, and terpenoids. The total phenolic and flavonoid contents in both 2 and 3 years old leaves of S. mahagoni ranged from 36.4 ± 0.84 to 42.0 ± 0.18 mg GAE/g dried extract and from 2.24 ± 0.15 to 18.55 ± 1.05mg QE/g dried extract, respectively. Also, the antioxidant values were 66.45 ± 1.85% and 77.59 ±11.23%, respectively. Based on the results, the antioxidant activity of S. mahagoni leaves was indicated as a result of the presence of α-tocopherol and α-tocopherolquinone in the leaves extracts.